Survey of Completeness of Facilities and Infrastructure and Implementation of The Trias UKS Program in SMAN, SMKN, and MAN All of Jombang Subdistrict, Jombang District Academic Year 2022/2023 - Puguh Satya Hasmara (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
UKS is the main channel of health education in schools to improve the ability to live a healthy life and form healthy behaviors that will later produce an optimal degree of health of students. Schools where coaching and health learning are distributed, but sometimes school conditions have not become a priority for school residents, and so far there has been no research on facilities and infrastructure and the implementation of the UKS program in Jombang District. The study aims to determine the completeness of facilities and infrastructure as well as the implementation of the Trias UKS program in SMAN, SMKN, and MAN in Jombang District, Jombang Regency, for the 2022/2023 academic year. Data collection techniques use observation sheets, documentation questionnaires, and interviews. A sample of all members of the population amounted to 8 schools in Jombang District. The data analysis technique used is quantitative descriptive analysis with percentages. The result of the study is that all schools get a very high category. The highest percentage was 100%, obtained by SMAN 3 Jombang. Meanwhile, the lowest percentage was obtained by MAN 8 Jombang with a percentage of 83%. The conclusion of this study is that the overall category is very high. The highest percentage in SMAN institutions is found in SMAN 3 Jombang with a percentage of 100%. Meanwhile, the highest percentage at the SMKN institution was achieved by SMKN 1 Jombang with a percentage of 99%. Meanwhile, the highest percentage gain in MAN institutions was produced by MAN 1 Jombang with a percentage of 99%. With his knowledge, it is hoped that it will be able to improve the quality of UKS, both in the completeness of facilities and infrastructure as well as the implementation of the Trias UKS program.